THE EFFECTS OF MOTIVATION AND SELF-EFFICACY ON SANTRI'S SELF-REGULATED LEARNING IN MEMORIZING AL-QUR'AN - Luk-Luk Nur Mufidah; Anissatul Mufarohah (Paedagogia: Jurnal Pendidikan, 2023)
The purpose of this study is to examine and describe the level of motivation, self-efficacy, and self-regulation of students memorising the Koran at Al-Bahjah Islamic boarding school Karangrejo Tulungagung, as well as to investigate the effect of motivation and self-regulation on self-regulated students memorising the Koran at Al-Bahjah Islamic boarding school Karangrejo Tulungagung. This study is a correlational study since it sought to determine the relationship between three factors, namely motivation, self-efficacy, and self-regulated learning, in Islamic boarding school pupils at al-Bahjah Karangrejo Tulungagung, East Java. According to the findings of this study, Santri memorising the Qur'an at Islamic boarding school al-Bahjah 3 Tulungagung had a high category of memorising motivation of 34% (17 people), a moderate category of 54% (27 people), and a low category of 13%. (6 people). Santri memorizers at al-Bahjah 3 Tulungagung Islamic boarding school with a high self-efficacy category of 10% (5 people), moderate self-efficacy category of 82% (41 people), and low self-efficacy category of 8% (4 people). Santri memorizers at Tulungagung's al-Bahjah Islamic boarding school have a high self-regulation category of 16% (8 people), a moderate category of 82% (41 people), and a low category of 2%. (1 person). There are numerous contributing aspects, like pesantren laws and memorising targets that students must own. There are several restrictions at Al-Bahjah Islamic Boarding School, as well as schedules and goals for memorising the Quran. Under this circumstance, pupils lack flexibility in managing themselves in order to reach the intended goals of memorising the Qur'an.